A convergência entre o trabalho em condições análogas à escravidão e a vulnerabilidade atrelada à imigração no Brasil - Mallmann, Tainara Mariana (2024)
This dissertation analyzes certain vulnerability factors that can result in immigrants being subjected to work relationships analogous to slavery in Brazil. It is known that immigrants constitute one of the most vulnerable groups in contemporary times, as their fundamental rights are often denied by the State and society. The inclusion of immigrants in the national labor market highlights the subject of certain workers being subjected to degrading and inhumane working conditions. It is possible to state that immigrants are especially affected by working in conditions similar to slavery in Brazil today, so the research problem presented refers to the identification of conditions that have the capacity to contribute to this scenario. The objective, therefore, is to describe factors that may contribute to the exploitation of immigrant labor in conditions similar to slavery in Brazil. The procedure used consists of the use of essentially bibliographical research, carried out through the collection and examination of materials coming from mostly secondary sources, in addition to the analysis of some information coming from primary research sources – collected through the Access to Information Law. The theme is relevant because the constant migratory flows in Brazil end up generating several challenges in terms of inserting these individuals into the national job market in conditions of dignity. This often means that immigrants are subjected to degrading and inhumane working conditions, making it necessary for the problem to be highlighted and put on the agenda so that the need to guarantee the rights of this portion of the population remains explicit. In the end, it is concluded that immigrants are vulnerable to working in conditions similar to slavery in Brazil due to factors such as racism, difficulty in regularizing their immigration status and revalidating diplomas.